Job satisfaction of general nurses in standard and intensive care units: "The nurse is a jack-of-all-trades!" - Glajchová, Alena; Hlaváčková, Eva; Holá, Jana; Moravcová, Markéta (My University, 2021)
New trends in providing healthcare are dynamically changing the field and increasing demands on healthcare staff. The adequate capacity and training of healthcare staff is considered an essential measure of the quality of the provided care. The shortage of health personnel is becoming one of the most pressing issues and challenges facing both the health system and society as a whole. The aim of this text is to shed light on how general nurses perceive their profession and what influences their level of job satisfaction. To this end, qualitative research was conducted and the method of in-depth interviews was used to determine the experiences of general nurses (working in standard and intensive care units) in their profession. The general nurses evaluated the issues of their work through aspects related mainly to management, teamwork, working conditions, competency, adaptation process, prestige and respect. There is an interplay between the various factors that affect the subjectivity of general nurses in different situations and with different intensities. General nurses perceive higher financial remuneration as a motivation, but not as a major predictor of their job satisfaction. Nurses interpreted the key factors for job satisfaction to be communication and collaboration.
Pracovní spokojenost všeobecných sester na oddělení standardní a intenzivní péče: „Ta sestra je pro všechno!“
Keywords: communication; general nurses; job satisfaction; management; shortage of nurses; komunikace; management; nedostatek sester; pracovní spokojenost; všeobecné sestry